2019
DOI: 10.1016/j.learninstruc.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy of success, attainment value, engagement, and Achievement: A moderated mediation analysis

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 61 publications
(39 reference statements)
8
65
1
5
Order By: Relevance
“…The relation between control and enjoyment was amplified by low intrinsic value. This is similar to interactions shown in studies of expectancy-value theory (Guo, Marsh, Parker, Morin, & Yeung, 2015;Putwain, Nicholson, Pekrun, Becker, & Symes, 2019), whereby higher value shows a protective role at low control that diminishes at higher levels of control. The protective role of high intrinsic value on enjoyment at lower control is harder to discern in the present study, due to the large first-order effect of intrinsic value.…”
Section: Discussionsupporting
confidence: 84%
“…The relation between control and enjoyment was amplified by low intrinsic value. This is similar to interactions shown in studies of expectancy-value theory (Guo, Marsh, Parker, Morin, & Yeung, 2015;Putwain, Nicholson, Pekrun, Becker, & Symes, 2019), whereby higher value shows a protective role at low control that diminishes at higher levels of control. The protective role of high intrinsic value on enjoyment at lower control is harder to discern in the present study, due to the large first-order effect of intrinsic value.…”
Section: Discussionsupporting
confidence: 84%
“…The MCT theoretical model was created by Valenzuela et al (2011) based on the work of Wigfield and Tonks (2009). The model presents the concept of MCT using the elements expectancy and value, and the subelements attainment, interest, utility, and cost (Galla et al, 2018;Putwain et al, 2019;Rosenzweig & Wigfield, 2017;Valenzuela et al, 2011Valenzuela et al, , 2014Wigfield & Gladstone, 2019;Wigfield & Tonks, 2009). The expectancy represents the importance that nursing students assign to CT in the disciplinary and professional nursing context.…”
Section: Introductionmentioning
confidence: 99%
“…Utility refers to how the achieved nursing experience can be used for future nursing care. Cost is conceptualized in terms of the amount of effort needed to think critically in nursing contexts when nursing care is provided (Galla et al, 2018;Putwain et al, 2019;Rosenzweig & Wigfield, 2017;Valenzuela et al, 2011Valenzuela et al, , 2014Wigfield & Gladstone, 2019;Wigfield & Tonks, 2009) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence from self-reports of the activities preceding the test indicated that students who practiced outcome simulation rehearsed the delight they would experience from obtaining a good mark but failed to put more effort into achieving the good mark, thereby ultimately reducing their aspirations. Positive expectations motivate learning in students, leading to enhanced performance through behavioral engagement (Putwain et al, 2019). Behavioral engagement is an omnibus variable that includes effort, persistence, and exertion in class activities (Appleton et al, 2006;Fredricks et al, 2004).…”
Section: Introductionmentioning
confidence: 99%